2016
DOI: 10.5152/jtgga.2015.0185
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of post-cesarean section incisional infiltration with lidocaine and epinephrine versus lidocaine alone in reducing postoperative pain: A randomized controlled double-blinded clinical trial

Abstract: Administering epinephrine with 2% lidocaine prolongs the anesthetic effect and reduces the opioid analgesic dose postoperatively required, thereby enhancing patient recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…158 Risk for surgical site infection is not increased, but these studies have not been powered for this outcome. 159 Continuous wound infusion is less effective than parenteral morphine and NSAIDs. 158 Most trials have not included neuraxial morphine comparisons, so no definitive comments can be made about superiority to neuraxial morphine.…”
Section: Anesthesia For Cesarean Deliverymentioning
confidence: 99%
“…158 Risk for surgical site infection is not increased, but these studies have not been powered for this outcome. 159 Continuous wound infusion is less effective than parenteral morphine and NSAIDs. 158 Most trials have not included neuraxial morphine comparisons, so no definitive comments can be made about superiority to neuraxial morphine.…”
Section: Anesthesia For Cesarean Deliverymentioning
confidence: 99%
“…In parallel with our study, Tharwat et al ( 20 ) assessed the efficacy and safety of incisional infiltration of local lidocaine in patients undergoing CD. They demonstrated that lidocaine administration reduced the opioid analgesic dose postoperatively and enhanced patient recovery.…”
Section: Discussionmentioning
confidence: 71%
“…3% chloroprocaine with epinephrine compared to 2%lidocaine with epinephrine showed [46] a long duration and best surgical analgesia with lidocaine2% and epinephrine. Through these findings, we deduce that lidocaine 2% is a best choice for epidural elective CD, all the more so, if epinephrine was added on it [4] . The advantages of using lidocaine in EPA for CD include his quick anesthesia onset, thereby avoiding GA and threaten side effectsassociated, when occurring.…”
Section: Discussionmentioning
confidence: 80%
“…Recent researches showed that more than 32% [35% in USA [1] ;32,5 in Ethiopia, Africa [2] , 32% in Thailand [3] of women, give birth under cesarean section [CS]. The trend is increasing [1] and even reached 46% in China according to the results of a study published in 2016 [4] . Many cesarean deliveries [CD] are performed under neuraxial anesthesia using local anesthetics [LAs] [2] .…”
Section: Introductionmentioning
confidence: 99%